2016
DOI: 10.1021/acs.joc.6b01705
|View full text |Cite
|
Sign up to set email alerts
|

Development of N-Substituted Hydroxamic Acids with Pyrazolone Leaving Groups as Nitrosocarbonyl Precursors

Abstract: A novel class of nitrosocarbonyl precursors, N-substituted hydroxamic acids with pyrazolone leaving groups (NHPY), has been synthesized. Under physiological conditions, these compounds generate nitrosocarbonyl intermediates, which upon hydrolysis release nitroxyl (azanone, HNO) in excellent yields. The amount and rate of nitrosocarbonyl generation are dependent on the nature of the pyrazolone leaving groups and significantly on the structural properties of the NHPY donors. Pyrazolones have been found to be eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…OHPY is very small, observed half-lives should correlate with donor pKa and the pyrazolone leaving group 19,20. Pyrazolone 2a (R 1 = Ph, R 2 = (C(=NOMe)Me, pKa = 6) is a better leaving group than pyrazolone 2b (R 1 = Ph, R 2 = Me, pKa = 7.6),19 consistent with the much shorter half-life for OHPY 1a (t1/2 = 25 min) compared with 1b (stable).Exchanging the R 1 group from phenyl to methyl(OHPY 1c vs. 1d)increases the half-life by a factor of two, consistent with that previously reported for analagous HAPY and NHPY donors 19,47. A comparison of the known pKa values of the related compounds,…”
supporting
confidence: 87%
See 4 more Smart Citations
“…OHPY is very small, observed half-lives should correlate with donor pKa and the pyrazolone leaving group 19,20. Pyrazolone 2a (R 1 = Ph, R 2 = (C(=NOMe)Me, pKa = 6) is a better leaving group than pyrazolone 2b (R 1 = Ph, R 2 = Me, pKa = 7.6),19 consistent with the much shorter half-life for OHPY 1a (t1/2 = 25 min) compared with 1b (stable).Exchanging the R 1 group from phenyl to methyl(OHPY 1c vs. 1d)increases the half-life by a factor of two, consistent with that previously reported for analagous HAPY and NHPY donors 19,47. A comparison of the known pKa values of the related compounds,…”
supporting
confidence: 87%
“…We have recently found that pyrazolones are efficient traps for nitrosocarbonyl intermediates to generate N-substituted hydroxamic acid derivatives with pyrazolone leaving groups (NHPY) in a reversible manner. 47 In the current work, we observe OHPY decomposition to generate nitrosocarbonyls which further react with pyrazolones to produce isomeric NHPY compounds (Scheme 1). We have synthesized and studied NHPY compounds independently, and have recently demonstrated the efficient formation of nitrosocarbonyl intermediates upon decomposition of these compounds.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations